"Cancer risk after breast proton therapy considering physiological and radiobiological uncertainties" by Raptis et al. (Physica Medica 76 (2020) 1–6). (December 2020) - Paganetti, Harald
Highlights: The work by Raptis et al. shows an advantage of proton therapy for breast cancer with respect to second cancer induction. The reported values are lower than those reported in other publications for both photon and proton treatments. The authors found that motion and radiobiological uncertainties did not change the advantage of protons over photons. Treatment for breast cancer patients should consider second cancer risk together with other complication probabilities. Abstract: The paper by Raptis et al. concludes that proton therapy has an advantage over photon therapy with respect to the induction of a second cancer. Furthermore, the authors conclude that physiological movements and radiobiological parameters do not affect the general trend of lower risk associated with proton therapy. The work is based on a modeling framework which is different from most previously used models on the same subject. This invited commentary puts the findings of the paper in context with other published modeling studies on second cancer risk after proton and photon radiation therapy for breast cancer.